(untitled) (Tempo e Argumento, 2026)
This article presents a historical perspective on the creation of the Plurinational State of Bolivia in 2009. It takes advantage of the “social alternative” meaning of such an achievement in the international repercussion to make considerations about the Bolivian historical imagination at the turn of the last century. The following question guides the text’s reflections: Was Bolivia destined to become a Plurinational State because it has an indigenous population? Seeking to avoid determinism, the article focuses on the contingencies and uncertain bets of subjects and collectives who knew how to negotiate with hegemonies and agree on agreements and actions within a political vocabulary common to modern states. It presents and offers interpretations of the theories and concepts proposed by intellectuals, as well as the subversions and impasses of the demands of social movements and other political organizations.